Mobile device-based shaft speed estimation. (January 2017) - Rzeszucinski, Pawel; Lewandowski, Daniel; Pinto, Cajetan T.
Abstract: One of the fundamental parameters that needs to be fed into a rotating machinery condition monitoring system is the rotational speed of shaft operating in the system. This parameter is essential in order to derive other characteristic frequencies that may contain some valuable diagnostic information. There are many dedicated hardware elements used in determining the rotational speed of elements however the installation of them usually translates to additional cost of the entire condition monitoring scheme, especially if retrofitting is concerned, and may not always be financially viable due to potentially long payback period on the investment, as in the case of e.g. LV induction motors. This text investigates the possibility of assessing the rotational speed of a shaft based solely on the capabilities of a standard, off-the-shelf mobile phone. The results presented in this text seem to indicate that with an appropriate signal processing approach, it is possible to ascertain the speed of the rotating element using a tool available nowadays to virtually all service technicians.